MOTIVASI VOLUNTEER SEBUAH STUDI DESKRIPTIF PADA CSO PENDIDIKAN ANAK MARJINAL DAN JALANAN - Anggun Pesona Intan; Rike Penta Sitio (Jurnal Manajemen, 2016)
Volunteers give their service without expecting any monetary benefit. Despite of the absence of benefits, many of them were moved to becoming a volunteer in different social institutions. Therefore, many civil society organizations (which further called CSO) are depend on the involvement of volunteers, such as Terminal Hujan and Yayasan Sahabat Anak who are much depend on the engagement of volunteers in their daily activities to run the organization. The underlying reason why people are willing to do a volunteering activities can be divided as internal and external motivation. The aim of this study was to dig internal and external motivation of volunteers who stay and allocate their time to fully involved in CSO running for marginal children education movement. This research is an embedded single case qualitative study, with unit analysis individual volunteer who has been participating and serving the CSOs for at least three years. Furthermore, this study was conducted in participatory observation and interview using open-ended questionnaire to volunteers of Terminal Hujan and Yayasan Sahabat Anak. Regarding the result of the study, volunteers stay due to internal motivation factors, such as personal satisfaction, similar personal and organizational values, concern for the beneficiaries’ future, and need for soft skill improvement. However, external motivation as the presence of training from organizations and organizational management system also strengthening volunteers’ motivation to stay.